The effect of antiretroviral therapy provision on all-cause, AIDS and non-AIDS mortality at the population level - a comparative analysis of data from four settings in Southern and East Africa - Floyd, Sian; Herbst, Abraham Jacobus; Bärnighausen, Till; Zaba, Basia (Tropical medicine & international health, 2012)
Objective  To provide a broad and up-to-date picture of the effect of antiretroviral therapy (ART) provision on population-level mortality in Southern and East Africa. Methods  Data on all-cause, AIDS and non-AIDS mortality among 15-59 year olds were analysed from demographic surveillance sites (DSS) in Karonga (Malawi), Kisesa (Tanzania), Masaka (Uganda) and the Africa Centre (South Africa), using Poisson regression. Trends over time from up to 5 years prior to ART roll-out, to 4-6 years afterwards, are presented, overall and by age and sex. For Masaka and Kisesa, trends are analysed separately for HIV-negative and HIV-positive individuals. For Karonga and the Africa Centre, trends in AIDS and non-AIDS mortality are analysed using verbal autopsy data. Results  For all-cause mortality, overall rate ratios (RRs) comparing the period 2-6 years following ART roll-out with the pre-ART period were 0.58 (5.9 vs. 10.2 deaths per 1000 person-years) in Karonga, 0.79 (7.2 vs. 9.1 deaths per 1000 person-years) in Kisesa, 0.61 (6.7 compared with 11.0 deaths per 1000 person-years) in Masaka and 0.79 (14.8 compared with 18.6 deaths per 1000 person-years) in the Africa Centre DSS. The mortality decline was seen only in HIV-positive individuals/AIDS mortality, with no decline in HIV-negative individuals/non-AIDS mortality. Less difference was seen in Kisesa where ART uptake was lower. Conclusions  Falls in all-cause mortality are consistent with ART uptake. The largest falls occurred where ART provision has been decentralised or available locally, suggesting that this is important.